First Derivative Spectrophotometric Determination of Demeclocycline and Minocycline in Clinical Samples, Urine and Honey - Prasad, A Raghavendra Guru; Rao, V Suryanarayana (Scientific World, 2010)
The authors present simple and rapid method for the first derivative spectrophotometric determination of demeclocycline (DMC) and minocycline (MNC). The linear calibration function is established in the concentration range 10 to 50 μg/ml for DMC and 10 to 60 μg/ml for MNC. The proposed method is also applied for their resolution in synthetic binary mixtures. The resolution is based on the first derivative ultraviolet spectrophotometry with zero crossing measurement. The corresponding calibration function is linear in the rage 10 to 40 μg/ml for DMC and 10 to 50 μg/ml for MNC. The proposed methods are found to be selective, linear (R > 0.99), accurate (recovery = 98 to 104%) and precise (RSD < 1.1%) in the respective linear concentration ranges. The method is successfully applied for the analysis of these drugs in clinical samples, urine and honey without pretreatment. Keywords: Demeclocycline; Minocycline; First derivative; Resolution; Applications. DOI: 10.3126/sw.v8i8.3843 Scientific World Vol.8(8) 2010 pp.34-38